Platystele pamelae (Orchidaceae: Pleurothallidinae), a new species from Ecuador - Baquero R., Luis E.; Zuchan, Kilian (Lankesteriana: International Journal on Orchidology, 2017)
A new species of Platystele from the cloud forests of Northern Ecuador is described and illustrated. Platystele pamelae is compared to P. alucitae, a species that is overall similar and has been found growing sympatrically. The morphology of the leaves, the shape of the sepals and the intense sulphur-colored oblong lip, easily separate P. pamelae from P. alucitae and all other species in Platystele. Taxonomical and ecological notes are given.